THE ROLE OF SPORTS IN ACHIEVING SUSTAINABLE DEVELOPMENT GOALS - Gofurov Abduvokhid Makhmudovich; Mahmudjonov Asilbek Abduvokhid o‘g’li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
As mentioned above, one of the criteria for physical and spiritual maturity is the love of sports, its development. Huge sports facilities built in a number of cities and districts of our region – swimming pools, tennis courts, football fields-are a practical answer to the great of the president of the Republic to the field of sports development. Thanks to such opportunities and conditions, the prestige of our motherland before the world community is further elevated if sports become the Daily need of everyone, including children and adolescents, especially women.